Attenuation of Follicular Helper T Cell–Dependent B Cell Hyperactivity by Abatacept Treatment in Primary Sjögren's Syndrome. Issue 9 (13th August 2017) - Verstappen, Gwenny M.; Meiners, Petra M.; Corneth, Odilia B. J.; Visser, Annie; Arends, Suzanne; Abdulahad, Wayel H.; Hendriks, Rudi W.; Vissink, Arjan; Kroese, Frans G. M.; Bootsma, Hendrika
Abstract : Objective: To assess the effect of abatacept (CTLA‐4Ig), which limits T cell activation, on homeostasis of CD4+ T cell subsets and T cell–dependent B cell hyperactivity in patients with primary Sjögren's syndrome (SS). Methods: Fifteen patients with primary SS treated with abatacept were included. Circulating CD4+ T cell and B cell subsets were analyzed by flow cytometry at baseline, during the treatment course, and after treatment was completed. CD4+ effector T cell subsets and Treg cells were identified based on expression of CD45RA, CXCR3, CCR6, CCR4, CXCR5, programmed death 1, inducible costimulator (ICOS), and FoxP3. Serum levels of anti‐SSA/anti‐SSB and several T cell–related cytokines were measured. Expression of ICOS and interleukin‐21 (IL‐21) protein was examined in parotid gland tissue at baseline and after treatment. Changes in laboratory parameters and associations with systemic disease activity (EULAR Sjögren's Syndrome Disease Activity Index [ESSDAI]) over time were analyzed using generalized estimating equations. Results: Abatacept selectively reduced percentages and numbers of circulating follicular helper T (Tfh) cells and Treg cells. Other CD4+ effector T cell subsets were unaffected. Furthermore, expression of the activation marker ICOS by circulating CD4+ T cells and expression of ICOS protein in parotid gland tissue declined. Reduced ICOS expression on circulating Tfh cells correlated significantly with lower ESSDAI scores during treatment. Serum levels of IL‐21, CXCL13, anti‐SSA, and anti‐SSB decreased. Among circulating B cells, plasmablasts were decreased by treatment. After cessation of treatment, all parameters gradually returned to baseline. Conclusion: Abatacept treatment in patients with primary SS reduces circulating Tfh cell numbers and expression of the activation marker ICOS on T cells. Lower numbers of activated circulating Tfh cells contribute to attenuated Tfh cell–dependent B cell hyperactivity and may underlie the efficacy of abatacept.